2021
DOI: 10.1080/21645698.2021.1917975
|View full text |Cite
|
Sign up to set email alerts
|

Exploring potential of copper and silver nano particles to establish efficient callogenesis and regeneration system for wheat (Triticum aestivumL.)

Abstract: Ye (2021): Exploring potential of copper and silver nano particles to establish efficient callogenesis and regeneration system for wheat (Triticumaestivum L.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…The response of the related parameters to AgNO3 concentration assumed a more or less concentration-dependent bell-shaped curve peaked at 4 mg L −1 . With a genotype-dependent peak, the same trend was recorded for shoot regeneration in response to the increasing concentrations of AgNO3 in the potato cultivar 'Kufri Chipsona 1′ [25,26,39], tomato [40], primrose [41], oat [42], and wheat [43]. It was also observed dealing with shoot growth and chlorophyll content in potato [26] and robusta coffee [44].…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The response of the related parameters to AgNO3 concentration assumed a more or less concentration-dependent bell-shaped curve peaked at 4 mg L −1 . With a genotype-dependent peak, the same trend was recorded for shoot regeneration in response to the increasing concentrations of AgNO3 in the potato cultivar 'Kufri Chipsona 1′ [25,26,39], tomato [40], primrose [41], oat [42], and wheat [43]. It was also observed dealing with shoot growth and chlorophyll content in potato [26] and robusta coffee [44].…”
Section: Discussionsupporting
confidence: 59%
“…Moreover, the positive effect of AgNO 3 on in vitro growth of potato shoots was recorded by Turhan [46]. The AgNO 3 -related improvements in shoot regeneration, recorded at low concentrations, can be explained by interference with ethylene perception that ameliorates the inhibitory impact of the accumulation of the gas hormone on shoot regeneration [21,43] and shoot growth [47]. The current results reflected only 33% improvement in shoot regeneration % at 4 mg L −1 , while the average number of regenerated shoots per explant reached 2.5 folds of control.…”
Section: Discussionmentioning
confidence: 98%
“…Reduction in the morphogenic response observed with higher levels of the metals in the present study can be explained by the possible triggering effect they had on Fenton reaction that generates hydroxyl radicals which are known to cause lipid peroxidation, DNA and protein damage (Drazkiewicz et al 2004). In a study with AgNO 3 , CuSO 4 and their nanoparticles, Malik et al (2021) reported their differential promotory in uence on callus induction, embryogenic tissue formation and plant regeneration in Triticum aestivum genotypes in concentrationdependent manner, with the synthesized nanoparticles been more e cient over use of the two metals employed.…”
Section: Discussionmentioning
confidence: 99%
“…Our data contradict the aforementioned studies, but the observed discrepancy is not exceptional. Recently, Malik et al (2021) [24] reported that the calli of mature wheat embryos exposed to CuSO 4 concentrations in excess of the MS control medium showed a decrease in the frequency of somatic embryogenesis and plant regeneration. The addition of copper did not confirm the possibility of increasing regeneration in oat androgenic cultures [38] and reducing albinism in the barley microspore cultures [38].…”
Section: Discussionmentioning
confidence: 99%
“…The use of other plant growth regulators in conjunction with auxins may be useful to achieve a better balance between an efficient morphogenic response and the level of albino plant regeneration. Data from previous reports indicate that additional supplementation of cytokinin [21], an abscisic acid [22], a gibberellin inhibitor [23], or an ethylene inhibitor [24] positively affects the morphogenic response of embryo-derived cereal cultures, affecting the efficacy and the type of plant regeneration pathway.…”
Section: Introductionmentioning
confidence: 99%